Implementasi E-Learning Sejarah Kebudayaan Islam Pada Masa Pandemi COVID-19 Di MTsN 4 Gunungkidul - Ana Dwi Wahyuni; Uzwatun Hazana Nur Fajri (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2020)
The Covid-19 pandemic that hit Indonesia had an impact on the world of education so that the Central Ministry of Religion created a learning application in the form of E-Learning Madrasas for distance learning. MTs N 4 Gunungkidul stated that it was ready to learn with Madrasa E-Learning during the Covid-19 pandemic. Therefore, the purpose of this study is to describe the implementation of E-Learning during the Covid-19 pandemic at MTs N 4 Gunungkidul. This study uses a descriptive qualitative approach. Data collection techniques by conducting observations, interviews, questionnaires and documentation. The results showed that the implementation of Madrasah E-Learning in Islamic Cultural History Subjects during the Covid-19 pandemic at MTs N 4 Gunungkidul was able to implement E-Learning well. The implementation of Madrasah E-Learning is carried out in 3 stages: the preparation stage, the implementation stage and the evaluation stage. The strategy is in the use of Madrasah E-Learning features and in learning. Constraints are in the features of Madrasah E-Learning that need to be updated and perfected as well as network and internet quota constraints.